Detection of the florfenicol resistance gene floR in Chryseobacterium isolates from rainbow trout. Exception to the general rule?. Issue 4 (11th February 2017) - Verner-Jeffreys, David W.; Brazier, Thomas; Perez, Ramon Y; Ryder, David; Card, Roderick M.; Welch, Timothy J.; Hoare, Rowena; Ngo, Thao; McLaren, Nikki; Ellis, Richard; Bartie, Kerry L.; Feist, Stephen W.; et al.
Abstract: Bacteria from the family Flavobacteriaceae often show low susceptibility to antibiotics. With the exception of two Chryseobacterium spp. isolates that were positive for the florfenicol resistance gene floR, no clinical resistance genes were identified by microarray in 36 Flavobacteriaceae isolates from salmonid fish that could grow in ≥ 4 mg/L florfenicol. Whole genome sequence analysis of the floR positive isolates revealed the presence of a region that contained the antimicrobial resistance genes floR, a tet (X) tetracycline resistance gene, a streptothricin resistance gene and a chloramphenicol acetyltransferase gene. In silico analysis of 377 published genomes for Flavobacteriaceae isolates from a range of sources confirmed that well-characterised resistance gene cassettes were not widely distributed in bacteria from this group. Efflux pump-mediated decreased susceptibility to a range of antimicrobials was confirmed in both floR positive isolates using an efflux pump inhibitor (phenylalanine-arginine β-naphthylamide) assay. The floR isolates possessed putative virulence factors, including production of siderophores and haemolysins, and were mildly pathogenic in rainbow trout. Results support the suggestion that, despite the detection of floR, susceptibility to antimicrobials in Flavobacteriaceae is mostly mediated via intrinsic mechanisms rather than the horizontally acquired resistance genes more normally associated with Gram-negative bacterial pathogens such as Enterobacteriaceae. Abstract : The florfenicol resistance gene floR was found in a Chryseobacterium isolate recovered from a rainbow trout; analyses suggested horizontal acquisition and that this was a rare finding in this important group of aquatic bacteria.